2014
DOI: 10.1098/rsif.2014.0097
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to inhomogeneous static magnetic field beneficially affects allergic inflammation in a murine model

Abstract: Previous observations suggest that static magnetic field (SMF)-exposure acts on living organisms partly through reactive oxygen species (ROS) reactions. In this study, we aimed to define the impact of SMF-exposure on ragweed pollen extract (RWPE)-induced allergic inflammation closely associated with oxidative stress. Inhomogeneous SMF was generated with an apparatus validated previously providing a peak-to-peak magnetic induction of the dominant SMF component 389 mT by 39 T m 21 lateral gradient in the in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Politanski et al found no significant difference of cochlear ROS levels in male C57BL/6 mice between groups exposed to 5 mT SMF for each time-point (1, 3, 5, 7, 14 days) and controls, the activities of SOD/CAT enzymes were significantly elevated after exposure for three days, but not for other exposure time [ 44 ]. Cisllag et al found that exposure of human bronchial epithelial cells (A549) to inhomogeneous SMFs of 389 mT, either at lower or upper position, for 30 min, did not alter the levels of intrinsic ROS in PBS-treated cells, but could significantly decrease ROS level induced by ragweed pollen extract (RWPE) [ 38 ]. In addition, studies conducted in prokaryota ( E. coli and S. aureus ) observed no significant difference of ROS level after 100 mT exposure for 4 h [ 41 ].…”
Section: The Effects Of Magnetic Fields On Rosmentioning
confidence: 99%
“…Politanski et al found no significant difference of cochlear ROS levels in male C57BL/6 mice between groups exposed to 5 mT SMF for each time-point (1, 3, 5, 7, 14 days) and controls, the activities of SOD/CAT enzymes were significantly elevated after exposure for three days, but not for other exposure time [ 44 ]. Cisllag et al found that exposure of human bronchial epithelial cells (A549) to inhomogeneous SMFs of 389 mT, either at lower or upper position, for 30 min, did not alter the levels of intrinsic ROS in PBS-treated cells, but could significantly decrease ROS level induced by ragweed pollen extract (RWPE) [ 38 ]. In addition, studies conducted in prokaryota ( E. coli and S. aureus ) observed no significant difference of ROS level after 100 mT exposure for 4 h [ 41 ].…”
Section: The Effects Of Magnetic Fields On Rosmentioning
confidence: 99%
“…The interaction of static magnetic fields (SMF) with living organisms is a rapidly growing area of investigation . Many researchers have observed the effects of SMFs on tumor cells, lung, and bone deceases, allergy inflammation, etc., closely associated with oxidative stress.…”
Section: Micellar Effects In Liquid‐phase Oxidationmentioning
confidence: 99%
“…Micelles involving acetylcholine are of special interest, since acetylcholine is the most important neuromediator playing a substantial role in neuromuscular and cognitive activity of living beings. Magnetic effects in radical reactions including diffusion radical pares usually do not exceed 25% . The cause of the anomalously high (60–40%) magnetic effect may be explained by the formation of several types of diffusion radical pairs, which are sensitive to magnetic field.…”
Section: Micellar Effects In Liquid‐phase Oxidationmentioning
confidence: 99%
“…The sample size may seem to be low for even a pilot test. We conservatively (for normally distributed data) estimated 0% placebo effect based on an earlier study including a skin prick test for allergy on healthy volunteers applying a 15 min long local exposure with an identical SMF generator [16] as in the present trial and 75% SMF effect based on an in vivo animal experimental series of alcohol-induced ulcer in mice that has not yet been published, so we could keep 80% statistical power by a ¼ 5% and n ¼ 7/group. Inclusion criteria were as follows:…”
Section: Participants Recruitment Groups and Ethicsmentioning
confidence: 99%